Computer science reconsidered : - Fant, Karl M. (Wiley-Interscience, 2007)
The Invocation Model of Process Expression argues that mathematics does not provide the most appropriate conceptual foundations for computer science, but, rather, that these foundations are a primary source of unnecessary complexity and confusion._ It supports that there is a more appropriate conceptual model that unifies forms of expression considered quite disparate and simplifies issues considered complex and intractable._ This book presents that this model of process expression is alternative theory of computer science that is both valid and practical.